2014
DOI: 10.7717/peerj.555
|View full text |Cite
|
Sign up to set email alerts
|

Psoralidin induces autophagy through ROS generation which inhibits the proliferation of human lung cancer A549 cells

Abstract: Psoralidin (PSO), a natural furanocoumarin, is isolated from Psoralea corylifolia L. possessing anti-cancer properties. However, the mechanisms of its effects remain unclear. Herein, we investigated its anti-proliferative effect and potential approaches of action on human lung cancer A549 cells. Cell proliferation and death were measured by MTT and LDH assay respectively. Apoptosis was detected with Hoechst 33342 staining by fluorescence microscopy, Annexin V-FITC by flow cytometry and Western blot analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
(35 reference statements)
3
32
0
Order By: Relevance
“…The complex function of the p53 family members is tightly regulated at different levels including the interactions with a number of other proteins that often results in modifications of their stability, localization and transcriptional activities (Leãoa et al, 2014). Many factors can influence these variations, and in particular, regarding p53, several findings have reported the molecular links between apoptosis and ROS-mediated autophagy in A549 cells (Hao et al, 2014). p53 modulates autophagy through several routes: autophagy is repressed by the cytoplasmic localization of p53 in a non-transcriptional manner, whereas autophagy is enhanced by nuclear localization through transactivation of target genes including DRAM (Damage-Regulated Autophagy Modulator), a pro-autophagic and proapoptotic protein (Lorin et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The complex function of the p53 family members is tightly regulated at different levels including the interactions with a number of other proteins that often results in modifications of their stability, localization and transcriptional activities (Leãoa et al, 2014). Many factors can influence these variations, and in particular, regarding p53, several findings have reported the molecular links between apoptosis and ROS-mediated autophagy in A549 cells (Hao et al, 2014). p53 modulates autophagy through several routes: autophagy is repressed by the cytoplasmic localization of p53 in a non-transcriptional manner, whereas autophagy is enhanced by nuclear localization through transactivation of target genes including DRAM (Damage-Regulated Autophagy Modulator), a pro-autophagic and proapoptotic protein (Lorin et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, psoralidin treatment reduced the viability and promoted the apoptosis of SW480 cells in a dose-dependent manner. Furthermore, Hao et al (18) reported that psoralidin inhibited the proliferation of A549 cells by inducing ROS production. Szliszka et al (25) identified that psoralidin inhibited cell proliferation of prostate cancer cells by enhancement of tumor necrosis factor-related apoptosis-inducing ligand-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has revealed that psoralidin contains a number of compounds, including coumarin, flavonoids and monoterpene phenols, which possess immunomodulatory, anti-inflammatory, antioxidant and anti-tumor effects (17). Furthermore, Hao et al (18) reported that psoralidin inhibited the proliferation of A549 human lung cancer cells through the generation of reactive oxygen species (ROS). Additionally, psoralidin has been observed to inhibit cell proliferation and induce apoptosis of androgen-independent prostate cancer cells through phosphatidylinositol 3-kinase-mediated Akt signaling (17).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, psoralidin was additionally able to decrease the caspase-3 activity of Eca9706 cells in a dose-dependent manner. Hao et al (20) reported that psoralidin was able to inhibit the proliferation of A549 human lung cancer cells via generation of reactive oxygen species. Yang et al (17) reported that psoralidin was able to inhibit cell viability and induce apoptosis in human prostate cancer PC-3 and DU-145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hao et al (20) reported that psoralidin was able to inhibit the proliferation of human lung cancer A549 cells. The present study aimed to provide the first evidence of the anticancer effect of psoralidin on esophageal cancer, and render mechanistic insights into the antitumor action of this compound against human esophageal carcinoma Eca9706 cells.…”
Section: Introductionmentioning
confidence: 99%